Clodomiro Picado as a zoologist - Hilje, Luko (2025)
This article explores a little-known facet of Clodomiro Picado Twight: his contribution as a zoologist. While his most recognized legacy in Costa Rica is related to his investigations into venomous snakes and the production of anti-venom serums, he was also a prominent naturalist and pioneer in the study of national fauna. Since his childhood, Picado developed a deep curiosity about nature, cultivated later during his training in France, from where he acquired an integral vision of biological sciences. Upon his return to the country, in addition to his medical and teaching work, he forayed into zoology, focusing especially on herpetofauna. He documented numerous species of snakes, frogs and other vertebrates, combining field observation, scientific illustration and ecological analysis. His ability to integrate knowledge and his dexterity in the naturalist language made him an exceptional educator and an early reference in Costa Rican biology. The article underlines how Picado managed to articulate field biology with tropical medicine, anticipating current interdisciplinary approaches. Asimismo, its role is recognized as a precursor of environmental thinking and the value of Costa Rican biodiversity from a scientific and pedagogical perspective. In short, it stands out that Clodomiro Picado no solo must be remembered for his biomedical legacy, as well as one of the first modern zoologists and naturalists in the country. His life and work continues to be a source of inspiration for those seeking to understand and conserve the natural heritage of Costa Rica.